Egg consumption and risk of type 2 diabetes among African Americans: The Jackson Heart Study. Issue 3 (June 2016) - Djoussé, Luc; Petrone, Andrew B.; Hickson, DeMarc A.; Talegawkar, Sameera A.; Dubbert, Patricia M.; Taylor, Herman; Tucker, Katherine L.
Summary: Background & aims: Type 2 diabetes (DM) disproportionally affects African Americans. Data on the association between egg consumption and risk of DM are sparse. We sought to examine whether egg consumption is associated with the prevalence and incidence of DM among African Americans. Methods: We analyzed baseline data from 4568 participants of the Jackson Heart Study. Egg consumption was obtained using a food frequency questionnaire designed for this population. We used generalized estimating equations to calculate adjusted prevalence ratios of DM and Cox regression to estimate hazard ratios of DM with corresponding 95% confidence intervals (CI). Results: The average age was 55 ± 13 years and 64% of subjects were women. The median frequency of egg consumption was 2/week for men and 1/week for women. The prevalence of DM was 22% overall (21% of men and 23% of women). Multivariable adjusted prevalence ratio [PR (95% CI)] for DM were: 1.00 (ref), 1.14 (0.90–1.44), 1.33 (1.04–1.70), 1.33 (1.06–1.68), 1.26 (0.99–1.61), and 1.52 (1.17–1.97) for egg consumption of <1/month, 1–3/month, 1/week, 2/week, 3–4/week, and 5+/week, respectively, p for linear trend 0.0024. Corresponding multivariable adjusted hazard ratios were 1.00 (ref), 0.88 (0.65–1.19), 0.94 (0.68–1.30), 0.91 (0.66–1.25), 1.11 (0.81–1.52), and 1.17 (0.81–1.70), respectively, during a mean follow up of 7.3 years (p for linear trend 0.22). Conclusions: While egg consumption was positively associated with prevalent DM, prospective analysis did not show an association of egg intake with incidence of DM among African Americans.